2020
DOI: 10.1111/sum.12636
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon improvement under long‐term (36 years) no‐till sorghum production in a sub‐tropical environment

Abstract: Soil organic matter (SOM) is considered an important indicator of soil quality, which can be impacted by crop production practices such as tillage. In this study, two long‐term tillage regimes (conventional tillage [CT] and no tillage [NT], conducted for 36 years) were compared in continuous sorghum production in a sub‐tropical environment in southeast Texas. The positive effects of long‐term NT practice were more conspicuous at the soil surface compared with the deeper soil profiles. The SOC was greater (1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Soil represents the largest terrestrial carbon pool (Le Quere et al., 2018). Soil carbon storage is affected by farm management strategies (Chowaniak et al., 2020; Govindasamy et al., 2020; Singh & Whelan, 2020) and soil microbial processes can also result in the emission of N 2 O (Davidson, 2009; Hu et al., 2020; Wang et al., 2020), a greenhouse gas with 298 times the atmospheric heat‐trapping ability of CO 2 (IPCC, 2014). Biochar application increases soil organic content in soil, resulting in carbon sequestration (Zhao, Lin, et al, 2020).…”
Section: Biochar For Climate Change Mitigationmentioning
confidence: 99%
“…Soil represents the largest terrestrial carbon pool (Le Quere et al., 2018). Soil carbon storage is affected by farm management strategies (Chowaniak et al., 2020; Govindasamy et al., 2020; Singh & Whelan, 2020) and soil microbial processes can also result in the emission of N 2 O (Davidson, 2009; Hu et al., 2020; Wang et al., 2020), a greenhouse gas with 298 times the atmospheric heat‐trapping ability of CO 2 (IPCC, 2014). Biochar application increases soil organic content in soil, resulting in carbon sequestration (Zhao, Lin, et al, 2020).…”
Section: Biochar For Climate Change Mitigationmentioning
confidence: 99%
“…In addition to carbon sequestration, conservation tillage can reduce CO 2 emissions [60]. Accumulation of SOC exhibit a positive correlation with the sequestration of atmospheric CO 2 , while oxidation of SOC, as a result of practices such as tillage, can contribute to CO 2 emission from agricultural fields [48]. For example, CO 2 emission in conventional tillage was 29% greater than in no till in a loamy soil as reported by Bista et al [61].…”
Section: No-tillage and Conservation Agriculturementioning
confidence: 92%
“…Soil organic matter is considered an important indicator of soil quality and health, which can be impacted by crop production practices such as tillage [48]. Tillage has the potential to increase the rate of C mineralization through breaking larger macro aggregates, mixing crop residues and exposing protected SOC in the aggregates to soil microorganisms [5,6,49,50].…”
Section: No-tillage and Conservation Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…Conservation agriculture practices, such as zero tillage and residue retention, could potentially improve carbon sequestration in surficial soil (Dey et al., 2020). A 36‐year long‐term study found that no tillage resulted in 1.5 t C ha −1 of soil organic matter in comparison with conventional tillage (Govindasamy et al., 2021). Recent studies showed that microbial residue represents an important source of stable SOC (Kallenbach et al., 2016).…”
Section: Soil Carbon Sequestrationmentioning
confidence: 99%